2018
DOI: 10.1097/jhq.0000000000000148
|View full text |Cite
|
Sign up to set email alerts
|

Strategically Applying New Criteria for Use Improves Management of Peripheral Intravenous Catheters

Abstract: Peripheral intravenous catheters (PIVCs) are common devices used across many healthcare settings. This quality improvement project aims to proactively remove PIVCs as soon as possible by empowering nurses and providers to clinically evaluate the necessity of every PIVC on a daily basis on a general hospital medical unit. Specific criteria were established to assess PIVC necessity. Cases of PIVCs not meeting established criteria are escalated to providers for a decision point. The PIVC removal times documented … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…In modern day healthcare, hospital inpatients commonly require the insertion of vascular access devices, with an estimated prevalence of peripheral intravenous cannulation of up to 85% [1,2,3]. Hospitalized patients need a peripheral intravenous catheter to administer drugs, fluids, and blood products during their admission, and successful first-attempt peripheral intravenous cannulation ensures prompt administration of these drugs and fluids intravenously [1,2,3,4,5]. Although peripheral intravenous cannulation is the most common invasive hospital procedure performed worldwide, it is associated with an unacceptable high overall failure rate [5,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In modern day healthcare, hospital inpatients commonly require the insertion of vascular access devices, with an estimated prevalence of peripheral intravenous cannulation of up to 85% [1,2,3]. Hospitalized patients need a peripheral intravenous catheter to administer drugs, fluids, and blood products during their admission, and successful first-attempt peripheral intravenous cannulation ensures prompt administration of these drugs and fluids intravenously [1,2,3,4,5]. Although peripheral intravenous cannulation is the most common invasive hospital procedure performed worldwide, it is associated with an unacceptable high overall failure rate [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Intravenous therapy can be defined as any form of treatment in which access to a vein is necessary [1,6,8]. The procedure of peripheral intravenous cannulation is performed routinely in daily clinical practice, while the first attempt to obtain an intravenous access is not successful in every patient [2,4,5,8,9,10,11]. A recently published systematic review and meta-analyses reported a failure rate of up to 30% on the first attempt of peripheral intravenous cannulation with the conventional approach [6].…”
Section: Introductionmentioning
confidence: 99%
“…10 Recent studies have demonstrated the rates of idle PIVCs between 14% and 50%. 14,25,26 Staff awareness of the presence and appropriateness of an invasive device is the first crucial step for the prompt recognition and removal of unneeded devices. 17,27 In light of the negative consequences of forgotten devices for patients and health care services, quality improvement strategies and future studies are needed to explore systems' successes and failures in safety-related interventions and policy-related initiatives to enhance staff compliances and awareness of PIVCs.…”
Section: Discussionmentioning
confidence: 99%
“…Although rather simplistic in design and technique, peripheral intravenous catheterization is an invasive procedure that can lead to local (e.g., phlebitis, infiltration, hematoma, nerve puncture) and systemic complications (e.g., catheter-associated bloodstream infection [CRBSI], tip fracture and migration) [ 3 , 4 , 6 , 8 , 9 , 13 , 14 , 15 , 16 , 17 , 18 ]. These complications lead to premature catheter failure and an increase in morbimortality rates, workload for healthcare professionals, admission periods, and total care costs for the healthcare system [ 2 , 4 , 6 , 14 , 15 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The insertion of vascular access devices is a potential pathway for the entry of microorganisms into the bloodstream, which can lead to CRBSIs [ 11 , 13 , 19 ]. However, some recent studies showed that the PVC-related bloodstream infections (PVCR-BSIs) rates (0.1%, 0.5 per 1000 catheter-days) are lower than the other intravascular devices, such as CVCs (4.4%, 2.7 per 1000 catheter-days) and PICCs (2.4%, 2.1 per 1000 catheter-days) [ 7 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%